Characterization of Organo-Modified Bentonite Sorbents: The Effect of Modification Conditions on Adsorption Performance - Parolo, María Eugenia (2014)
The organic modification of a natural bentonite was evaluated using two methods: exchanging the interlayer cations by hexadecyltrimethylammonium (HDTMA) and grafting with vinyltrimethoxysilane (VTMS) and -methacryloyloxy propyl trimethoxysilane (TMSPMA) on montmorillonite surface. The physicochemical characterization of all materials was made by X-ray diffraction (XRD), IR spectroscopy, thermogravimetric analysis (TGA) and Brunauer–Emmett–Teller (BET) surface area techniques. HDTMA cations and organosilanes were intercalated into the interlayer space of montmorillonite, as deduced from the increase of the basal spacing. IR spectroscopy, TGA and BET area give evidence of successful organic modification. The studies show a decrease in the IR absorption band intensity at 3465 cm−1 with surfactant modification, and also a decrease of mass loss due to adsorbed water observed in two samples: the organoclay and functionalized bentonites, which are evidences of a lower interlayer hydrophilicity. The efficiency of aniline removal onto natural bentonite, organobentonite and functionalized bentonites from aqueous solutions was evaluated. Aniline sorption on natural bentonite was studied using batch experiments, XRD and IR spectroscopy. The hydrophobic surface of organobentonite and functionalized bentonites increased the retention capacity for nonionic organic substances such as aniline on bentonites. The sorption properties of modified bentonite, through different modification methods, enhanced the potential industrial applications of bentonites in water decontamination.